Hybrid Mean Value of the Hyper Cochrane Sums (Communications in Mathematical Research, 2021)
The main purpose of this paper is to use the analytic methods to studythe hybrid mean value involving the hyper Cochrane sums, and give several sharpasymptotic formulae.
Keywords: hyper Cochrane sum; hyper-Kloosterman sum; hybrid mean value.